Effects of a preseason triphasic resistance training program on athletic performance in elite volleyball players - an observational study - Rebelo, A.; Pereira, J. R.; Valente-dos-Santos, J. (German Journal of Exercise and Sport Research, 2023)
Volleyball is a sport that requires high levels of maximal strength, reactive strength, and power at the elite level. Various training methods exist to maximize these physical qualities. The purpose of the triphasic training method is to maximize sport performance by enhancing all three muscle actions to create a strong link between eccentric, isometric, and concentric phases. The purpose of this study is to assess the impact of a 6-week (three times per week) triphasic resistance training program during the preseason period in professional male volleyball athletes. Fourteen male elite volleyball players (mean [±standard deviation] age: 28.88± 5.59 years; height: 192± 10cm; body mass: 88.00± 14.54kg) completed several body composition assessments and physical tests. Squat jump performance (p= 0.02, d= 0.27, 3.16%) and both lower (p< 0.001, d= 0.71, 16.56%) and upper body (p= 0.002, d= 0.45, 7.98%) maximal strength significantly increased from pre to post intervention. Strength and conditioning professionals should consider this type of training if they seek to improve maximal strength and concentric power. However, if the goals are to improve reactive strength and change-of-direction speed, then coaches must shift towards a power-type training to improve these stretch-shortening cycle activities.